2005
DOI: 10.1007/s11103-005-0889-z
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Expression of Recombinant Proteins in Physcomitrella patens by a Conditional Heat-shock Promoter: a Tool for Plant Research and Biotechnology

Abstract: The ability to express tightly controlled amounts of endogenous and recombinant proteins in plant cells is an essential tool for research and biotechnology. Here, the inducibility of the soybean heat-shock Gmhsp17.3B promoter was addressed in the moss Physcomitrella patens, using b-glucuronidase (GUS) and an F-actin marker (GFP-talin) as reporter proteins. In stably transformed moss lines, Gmhsp17.3B-driven GUS expression was extremely low at 25°C. In contrast, a short non-damaging heat-treatment at 38°C rapid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
118
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 92 publications
(123 citation statements)
references
References 64 publications
(73 reference statements)
5
118
0
Order By: Relevance
“…2A and 3). This lower calcium transient correlated well with the consequent milder activation of the Hsp17.3B promoter observed in HSP-GUS line 28 grown at the same temperatures and submitted to 1 h heat shock at 35°C (Fig. 2B).…”
Section: Heat-induced Ca 2+ Influx Is Influenced By the Growth Tempersupporting
confidence: 76%
See 3 more Smart Citations
“…2A and 3). This lower calcium transient correlated well with the consequent milder activation of the Hsp17.3B promoter observed in HSP-GUS line 28 grown at the same temperatures and submitted to 1 h heat shock at 35°C (Fig. 2B).…”
Section: Heat-induced Ca 2+ Influx Is Influenced By the Growth Tempersupporting
confidence: 76%
“…Physcomitrella patens (Gransden wild type) was grown on moss solid minimal medium overlaid with a cellophane disk as in Saidi et al 28 and maintained in a temperature-controlled chamber at indicated temperatures…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The consequence of loss of function of the ARP3a gene on the organization of the actin cytoskeleton was studied in the previously described HGT1 strain that carries a heat shock inducible GFP-talin reporter construct [Finka et al, 2007;Saidi et al, 2005]. The Hyg R HGT1 Fig.…”
Section: Actin Organization In Arp3a Mutant Lines Is Affectedmentioning
confidence: 99%